1978
DOI: 10.1111/j.1471-4159.1978.tb02668.x
|View full text |Cite
|
Sign up to set email alerts
|

Citrate as the Precursor of the Acetyl Moiety of Acetylcholine

Abstract: Abstract— Rat brain cortex slices were incubated with glucose labeled with either 3H or 14C in the 6‐position. The 3H/14C ratios and the incorporation of radioactivity into lactate, citrate, malate and acetylcholine were determined. While the 3H/14C ratio of lactate was close to that of glucose, the ratios in the acetyl moiety of acetylcholine and the acetyl (C‐4,5) portion of citrate decreased in a similar proportion. This was interpreted as indirect evidence for the participation of citrate as a precursor to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 22 publications
5
22
0
Order By: Relevance
“…The effect of low dose chronic Pb2+ exposure on general metabolism and subsequent ACh synthesis in cerebral cortex slices was examined by using mixed-labeled substrates (See Sterling and O'Neill, 1978;Sterling et al, 1981 for details). The technique is based on the fact that one of the three hydrogens of the methyl group of acetyl-CoA is removed in its condensation with oxaloacetate in the formation of citrate, thereby lowering the "H/14C ratio in citrate to 0.67 (computed to a glucose ratio of I .OO).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of low dose chronic Pb2+ exposure on general metabolism and subsequent ACh synthesis in cerebral cortex slices was examined by using mixed-labeled substrates (See Sterling and O'Neill, 1978;Sterling et al, 1981 for details). The technique is based on the fact that one of the three hydrogens of the methyl group of acetyl-CoA is removed in its condensation with oxaloacetate in the formation of citrate, thereby lowering the "H/14C ratio in citrate to 0.67 (computed to a glucose ratio of I .OO).…”
Section: Resultsmentioning
confidence: 99%
“…1936;Browning and Shulman, 1968;Tutek and Cheng, 1974). cytosol and cleaved to AcCoA by ATP-citrate lyase (Sterling and O'Neill, 1978;Sterling et al, 1981). Several mechanisms for the transport of acetyl units across the mitochondrial membrane to the cytosol have been proposed (Jope, 1979;Doleial and Tutek, 1981;Tutek et al, 1981).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AcetylCoA is synthesized in peroxisomes and mitochondria, the intramitochondrial acetylCoA can pass the inner mitochondrial membrane in the form of citrate, delivering acetylCoA to cytosol, due to the action of citrate lyase. It was, however, demonstrated that citrate pathway supplied not more than 30% of acetyl moieties for acetylcholine synthesis in mammalian brain (Gibson and Shimada, 1980;Sterling and O'Neill, 1978;Tu cek et al, 1981). The works of Tu cek and his collaborators demonstrated that acetylcarnitine can be a source of acetyl groups for acetylcholine synthesis Tu cek, 1985Tu cek, , 1990, moreover being a better precursor than citrate Cheng, 1970, 1974;Tu cek et al, 1981).…”
Section: Acetylcarnitinementioning
confidence: 95%
“…Hence, PC is considered to have an impact on a multitude of processes, which are directly or indirectly dependent on the availability of oxaloacetate and other members of the TCA cycle, i.e., gluconeogenesis [4] and glycogen synthesis [5,6], lipogenesis [7,8], biosynthesis of non-essential amino acids with impact on the cellular/tissue nitrogen balance [9,10], the metabolism and the mitochondriacytosol shuttling of acetyl-CoA [4], and the regeneration of NADPH [11]. Due to its anaplerotic role, PC in brain may contribute to maintaining a cytosolic level of acetyl-CoA that is required for the synthesis of the neurotransmitters acetylcholine [12], glutamate, and GABA [13,14].…”
Section: Introductionmentioning
confidence: 99%